The Politicization of Ghana's Energy Sector and Its Effects on Ghana's Economy - Amarh, Benjamin Ashitey (Advances in Social Sciences Research Journal, 2025)
The document examines the impact of political involvement in Ghana's energy sector on the country's economy and environment. When politicians make decisions and appoint individuals to key roles in the energy sector based on political affiliations and considerations, it leads to a number of problems such as inefficiency, higher costs, and a lack of focus on solutions or renewable energy sources. The paper provides examples from the past, such as the AMERI power deal and changes in fuel prices, to illustrate how political interference can lead to issues. The problems include inefficient energy use, high energy costs resulting from political decisions, and inadequate investment in renewable energy. The paper suggests solutions like making the decision process more transparent, creating independent groups to oversee the energy sector, choosing people for jobs based on skills instead of political connections, involving the public more in decision-making, planning for the long term in energy, supporting policies that encourage renewable energy, and fighting against corruption in the energy sector. The goal is to make Ghana's energy future more friendly to the environment, reliable, and efficient.